Аlternative local stratigraphical scales of the Upper Miocene of the Rostov Dome - D. A. Ruban (Известия высших учебных заведений: Геология и разведка)
Background. Definition of local stratigraphical units, the main of which are formations, is important for geological mapping and correct understanding of the composition of sedimentary complexes. This task is yet to be solved for some territories. Thus, Upper Miocene deposits extend widely across the Rostov Dome in the southwest of Russia; however, the definition of formations there is still in its nascent phase.Aim. Systematization of ideas about the local stratigraphical units of the Upper Miocene of the Rostov Dome, taking previous assumptions into account.Materials and methods. An analysis of ideas related to the definition of formations in the Upper Miocene of the Rostov Dome was carried out. These ideas were systematized with a focus on the validity of the units based on the current stratigraphical code.Results. An improved local stratigraphical scale of the Upper Miocene of the Rostov Dome is proposed. This scale implies defining the Taganrogskaya (Lower Sarmatian), Rostovskaya (Middle–Upper Sarmatian), Donskaya (lower Upper Maeotian), Merzhanovskaya (upper Upper Maeotian), and Aleksandrovskaya (Lower Pontian) formations. The correspondence of alternative units is shown: the Mokrochaltyrskaya and Berdanosovskaya formations correspond to the Rostovskaya Formation, while and the later proposed Rostovskaya Formation corresponds to the Donskaya and Merzhanovskaya formations. Discussion. The validity of the proposed local stratigraphical units is noted; the priority of defining the Taganrogskaya and Aleksandrovskaya formations is highlighted. The question of creating an automatic system for generalizing information about stratigraphical units is discussed.Conclusion. The need in the parallel existence of alternative local stratigraphical scales of the Upper Miocene of the Rostov Dome is absent. However, subdividing the relevant deposits requires further discussion and refinement.